2021
DOI: 10.32435/envsmoke/xibesymp.7
|View full text |Cite
|
Sign up to set email alerts
|

Catalogue of Aquatic Mites From the Minho River (Nw Iberian Peninsula)

Abstract: Acari are a subclass of chelicerate arthropods that includes mites and ticks. The present study focuses on the taxonomic diversity of aquatic mites in the Portuguese territory of the Minho Region. Our aim was to compile all available information and thus generate a list of species linking them to the site where they were recorded. Aquatic species were all those that live exclusively in the marine environment, deep sea, intertidal, freshwater, brackish water or in transitional environments with the terrestrial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The water mites of Portugal are still insufficiently known. Water mites of mainland Portugal and its archipelagos (Madeira and Azores) were studied by Barrois (1887Barrois ( , 1896, Koenike (1895), Thor (1898), Viets (1918), Lundblad (1941Lundblad ( , 1942Lundblad ( , 1954Lundblad ( , 1956, and Cantallo et al (2021Cantallo et al ( , 2022. The most recent check list of water mites of Portugal and its archipelagos was published by Cantallo et al (2022), who reported 93 hydrachnid species from 34 genera and 16 families.…”
Section: Introductionmentioning
confidence: 99%
“…The water mites of Portugal are still insufficiently known. Water mites of mainland Portugal and its archipelagos (Madeira and Azores) were studied by Barrois (1887Barrois ( , 1896, Koenike (1895), Thor (1898), Viets (1918), Lundblad (1941Lundblad ( , 1942Lundblad ( , 1954Lundblad ( , 1956, and Cantallo et al (2021Cantallo et al ( , 2022. The most recent check list of water mites of Portugal and its archipelagos was published by Cantallo et al (2022), who reported 93 hydrachnid species from 34 genera and 16 families.…”
Section: Introductionmentioning
confidence: 99%